To settle the equation, factor x^2-6x-55 using formula x^2+left(a+b ight)x+ab=left(x+a ight)left(x+b ight). To uncover a and also b, collection up a device to be solved.

You are watching: Factor x^2-6x

Since ab is negative, a and b have the opposite signs. Because a+b is negative, the an unfavorable number has greater absolute value than the positive. List all such integer bag that give product -55. x2-6x-55=0 Two solutions were uncovered : x = 11 x = -5 action by step solution : action 1 :Trying to element by splitting the middle term 1.1 Factoring x2-6x-55 The an initial term is, x2 that is ...
x2+10x+16=0 Two options were discovered : x = -2 x = -8 step by step solution : step 1 :Trying to element by splitting the center term 1.1 Factoring x2+10x+16 The very first term is, x2 the ...
-3x2-6x-5=0 Two solutions were uncovered : x =(6-√-24)/-6=1+i/3√ 6 = -1.0000-0.8165i x =(6+√-24)/-6=1-i/3√ 6 = -1.0000+0.8165i action by step solution : action 1 :Equation at the end of action 1 : ...
0=2x2-6x-56 Two remedies were discovered : x = 7 x = -4 Rearrange: Rearrange the equation by individually what is come the best of the equal sign from both political parties of the equation : ...
2x2-6x-25=0 Two solutions were discovered : x =(6-√236)/4=(3-√ 59 )/2= -2.341 x =(6+√236)/4=(3+√ 59 )/2= 5.341 step by step solution : action 1 :Equation in ~ the finish of action 1 : (2x2 - 6x) - 25 = ...
2x2-6x-95=0 Two solutions were found : x =(6-√796)/4=(3-√ 199 )/2= -5.553 x =(6+√796)/4=(3+√ 199 )/2= 8.553 step by step solution : action 1 :Equation at the finish of step 1 : (2x2 - 6x) - 95 ...
More Items     To fix the equation, element x^2-6x-55 utilizing formula x^2+left(a+b ight)x+ab=left(x+a ight)left(x+b ight). To find a and also b, collection up a device to be solved.
Since ab is negative, a and b have the opposite signs. Because a+b is negative, the negative number has better absolute worth than the positive. List all together integer pairs that give product -55.
To settle the equation, variable the left hand next by grouping. First, left hand side needs to be rewritten as x^2+ax+bx-55. To uncover a and b, set up a mechanism to it is in solved.
Since abdominal is negative, a and b have actually the the contrary signs. Due to the fact that a+b is negative, the negative number has better absolute worth than the positive. List all such integer pairs that provide product -55.
All equations of the type ax^2+bx+c=0 have the right to be fixed using the quadratic formula: frac-b±sqrtb^2-4ac2a. The quadratic formula offers two solutions, one as soon as ± is addition and one as soon as it is subtraction.
This equation is in traditional form: ax^2+bx+c=0. Substitute 1 for a, -6 for b, and also -55 because that c in the quadratic formula, frac-b±sqrtb^2-4ac2a.
Quadratic equations such as this one can be solved by perfect the square. In stimulate to complete the square, the equation must an initial be in the type x^2+bx=c.
Divide -6, the coefficient the the x term, through 2 to acquire -3. Then add the square the -3 to both sides of the equation. This step makes the left hand next of the equation a perfect square.

See more: An Archer Shoots An Arrow At A Target That Is A Horizontal Distance

Factor x^2-6x+9. In general, as soon as x^2+bx+c is a perfect square, it can constantly be factored together left(x+fracb2 ight)^2.
left< eginarray together l 2 & 3 \ 5 & 4 endarray ight> left< eginarray together l together 2 & 0 & 3 \ -1 & 1 & 5 endarray ight>    EnglishDeutschEspañolFrançaisItalianoPortuguêsРусский简体中文繁體中文Bahasa MelayuBahasa Indonesiaالعربية日本語TürkçePolskiעבריתČeštinaNederlandsMagyar Nyelv한국어SlovenčinaไทยελληνικάRomânăTiếng Việtहिन्दीঅসমীয়াবাংলাગુજરાતીಕನ್ನಡकोंकणीമലയാളംमराठीଓଡ଼ିଆਪੰਜਾਬੀதமிழ்తెలుగు